Kebijakan Fiskal pada Masa Rasulullah dan Sekarang - Ibnu Hasan Karbila; Abdul Helim; Rofii Rofii (STAI Auliaurrasyidin Tembilahan, 2020)
This study aimed at distinguishing fiscal policy during the time of the Prophet and the fiscal policy prevailing in Indonesia. The study method in this research is literature study. The type of data used is secondary data with data collection methods through literature study. The results showed that during the time of the Prophet, the first fiscal policy that was taken after moving to Medina was to make muhajirin and ansar fraternal and provide employment for the Muhajirin. In the second year, almsgiving and fitrah are compulsory, followed by zakat in the ninth year of hijriyah. From here emerged fiscal policy instruments derived from zakat, infaq, alms and waqf. Some of these elements are mandatory and some are voluntary. Zakat is an element that must be paid after reaching the nisab, while infaq, alms and waqf are voluntary. This voluntary element is what distinguishes an Islamic economy from a capitalist economy. Another difference between the two is related to the management of state money where part of the APBN sources obtained from debt must be free from the element of interest, thus, the state debt can actually be obtained in ways that are in accordance with Islamic Sharia